Schistosomal Cervical Myelopathy - Farias, Ronald; Oliveira, Kléver Forte de; Mendes, George de Albuquerque Cavalcanti; Meira, Ussânio Mororó (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2018)
Schistosomiasis is an infectious disease caused by trematode platyhelminths of the genus Schistosoma. The involvement of the cervical spinal cord is rare, with few cases reported in the literature. The management of such patients is particularly challenging, since clinical and radiological findings may be confounded with other inflammatory diseases and/ or spinal cord tumors. We describe a 20-year old male with a history of swimming outdoors. He first presented pain in the back of the neck extending to shoulders and upper limbs paresis associated with four limbs hyperreflexia. The magnetic resonance imaging (MRI) showed a hypointense T1-weighted lesion in the cervical spinal cord, which was hyperintense on T2 images. The serologic testing was negative for schistosomiasis. A cervical cord biopsy at the C5-C6 level showed Schistosoma eggs in the histopathological examination. The treatment was performed using a single dose of praziquantel 50 mg/kg, with prednisone 40 mg/day for 3 weeks. On the follow-up, 1 year later, the patient presented mild reduction of the vibratory sensitivity in the distal third of both legs. Our illustrative case strengthens that, in endemic regions, Schistosoma mansoni infestation should be included in the differential diagnosis of intramedullary expansive lesions.
Keywords: schistosoma mansoni; schistosomiasis; neuroschistosomiasis; cervical cord